2019
DOI: 10.1177/1526924819835840
|View full text |Cite
|
Sign up to set email alerts
|

Prior Amiodarone Exposure Reduces Tacrolimus Dosing Requirements in Heart Transplant Recipients

Abstract: Introduction: Amiodarone use prior to heart transplant is independently associated with a higher rate of severe primary graft dysfunction and in-hospital mortality. Amiodarone may also alter the pharmacokinetics of medications metabolized via cytochrome P450. No data exist regarding the interaction between pretransplant amiodarone and tacrolimus concentrations. Design: Single-center retrospective study of transplant patients between January 1, 2014, and June 30, 2016. A therapeutic tacrolimus concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Therefore, close drug trough level monitoring with dosage adjustment is essential to avoid overdosing or underdosing. In addition to amiodarone, several other factors may influence serum levels of cyclosporine A or tacrolimus including age, gender, weight, glomerular filtration rate, and concomitant medication 1,33–37 . In this study, we found no significant differences between patients with or without pre‐transplant amiodarone use in dosage or drug trough levels of cyclosporine A or tacrolimus within 30 days after HTX.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Therefore, close drug trough level monitoring with dosage adjustment is essential to avoid overdosing or underdosing. In addition to amiodarone, several other factors may influence serum levels of cyclosporine A or tacrolimus including age, gender, weight, glomerular filtration rate, and concomitant medication 1,33–37 . In this study, we found no significant differences between patients with or without pre‐transplant amiodarone use in dosage or drug trough levels of cyclosporine A or tacrolimus within 30 days after HTX.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to amiodarone, several other factors may influence serum levels of cyclosporine A or tacrolimus including age, gender, weight, glomerular filtration rate, and concomitant medication. 1,[33][34][35][36][37] In this study, we found no significant differences between patients with or without pre-transplant amiodarone use in dosage or drug trough levels of cyclosporine A or tacrolimus within 30 days after HTX. Moreover, we found no significant difference between both groups in terms of acute rejection as cause of death within 30 days after HTX (all P ≥ 0.05).…”
mentioning
confidence: 82%
“…AMD is metabolized through the CYP3A metabolic pathway, and it has been reported that patients receiving AMD prior to transplant require a reduction of the TAC dose [25]. It is therefore necessary to check blood levels of both AMD and TAC carefully.…”
Section: Calcineurin Inhibitors (Cnis)mentioning
confidence: 99%